2017
DOI: 10.1093/neuros/nyx293
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Efficacy of the Pipeline Embolization Device in the Treatment of Posterior Communicating Region Aneurysms with Fetal Posterior Cerebral Artery Configuration

Abstract: The PED is a safe and effective treatment for PcommA aneurysms, although fetal anatomy should increase consideration of traditional endovascular techniques or surgical clipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…Moreover, a lower rate of complete occlusion was observed in PcoA aneurysms coupled with fetal (vs non-fetal) types of PCA (66.7% vs 87.5%), although group differences were not significant (p=0.3) 26. Anil et al also found flow diversion less effective in occluding aneurysms with PcoA origins and fetal-type PCAs, citing fetal-type PCA as an independent risk factor (OR 73.65, 95% CI 5.84 to 929.13; p=0.001),27 and Adam et al achieved complete occlusion at a rate of only 33% after Pipeline embolization of PcoA aneurysms with fetal-type PCAs 28. Hence, fetal-type PCA seems to impact PcoA flow under these circumstances, limiting the occlusive potential of flow diversion.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a lower rate of complete occlusion was observed in PcoA aneurysms coupled with fetal (vs non-fetal) types of PCA (66.7% vs 87.5%), although group differences were not significant (p=0.3) 26. Anil et al also found flow diversion less effective in occluding aneurysms with PcoA origins and fetal-type PCAs, citing fetal-type PCA as an independent risk factor (OR 73.65, 95% CI 5.84 to 929.13; p=0.001),27 and Adam et al achieved complete occlusion at a rate of only 33% after Pipeline embolization of PcoA aneurysms with fetal-type PCAs 28. Hence, fetal-type PCA seems to impact PcoA flow under these circumstances, limiting the occlusive potential of flow diversion.…”
Section: Discussionmentioning
confidence: 97%
“…35 However, PED treatment of aneurysms incorporating the origin of a fetal PCA was largely ineffective, probably because the fetal PCA has low compensation capabilities and the residual pressure gradient might prevent the aneurysm from occluding. 36,37 Actually, flow diversion of aneurysms incorporating a fetal PCA should only be considered when conventional treatments are unfeasible. 37…”
Section: Bifurcation Aneurysmsmentioning
confidence: 99%
“…36,37 Actually, flow diversion of aneurysms incorporating a fetal PCA should only be considered when conventional treatments are unfeasible. 37…”
Section: Bifurcation Aneurysmsmentioning
confidence: 99%
“…But endovascular treatment of fetal PComA faces some challenges, specifically for the ruptured ones. Roy et al reported an independent association between incomplete occlusion and fPCA configuration [25]. Wallace et al reported a complication rate of 14% and overall complete occlusion rate of 33% [26].…”
Section: Discussionmentioning
confidence: 99%